Assessment of impact of climate change on potato and potential adaptation gains in the Indo-Gangetic Plains of India - Naresh Kumar, Soora; Govindakrishnan, P.M.; Swaroopa Rani, D.N.; Nitin Ch; Surabhi J; Aggarwal, Pramod K. (Gorgan University of Agricultural Sciences and Natural Resources, 2015)
India is the second largest producer of potato in the world. The Indo-Gangetic plains (IGP) is the main potato growing region accounting for almost 85% of the 1.8 Mha under the crop in India where it is grown as an irrigated crop during the winter season. Since IGP is in sub-tropical plains, duration of the thermally suitable window is the main determinant limiting yields. Hence the impact of climate change on potato in the IGP was assessed using MIROC HI.3.2 A1b and B1, PRECIS A1b, A2, B2 scenarios and estimated the potential adaptation gains. The potato crop duration in the IGP is projected to decrease due to climate change. The evapotranspiration (ET) is projected to increase while the water use efficiency (WUE) for potato yield is projected to decline in future climates as a consequence of low threshold temperatures for decline in WUE and yield than the ET. Results indicate that the upper threshold for ET decrease is ~23 oC while that for WUE is 15 oC. The optimal temperatures for tuber yield is ~17 oC and thus the reduction in WUE in future climates is discernable. Climate change is projected to reduce potato yields by ~2.5, ~6 and ~11% in the IGP region in 2020 (2010-2039), 2050 (2040-2069) and 2080 (2070-2099) time periods. Change in planting time is the single most important adaptation option which may lead to yield gains by ~6% in 2020 and its combination with improved variety or additional nitrogen may be required to adapt to climate change leading to positive gains by ~8% in 2020 and by ~5% even in 2050. However, in 2080 adoption of all the three adaptation strategies may be needed for positive gains. Intra-regional differences in the impact of climate change and adaptation gains are projected; positive impact in northwestern IGP, gains in Central IGP with adaptation and yield loss in eastern IGP even with adaptation.